From Talk to Thought: Strength of Ethnic Identity and Caregiver Mental State Talk Predict Social Understanding in Preschoolers. (October 2015) - Taumoepeau, Mele
In a sample of Pacific Island families living in New Zealand ( N = 45), this study tested the relation between caregivers' strength of ethnic identity and their use of desire, cognitive, and emotion language with their toddlers during a picture description task at 15, 20, 26, 33, and 39 months. Using multi-level growth modeling, caregivers' strength of ethnic identity predicted the change trajectories of caregivers' mental state talk over and above the effects of education levels, and these individual estimates were predictive of their children's performance on an emotion situation and knowledge access tasks at 39 months. We discuss the results in the light of theories regarding the role of culture and mental state language socialization of young children.